Viscosity and social cohesion in temporal lobe epilepsy. Issue 2 (February 1992) - Rao, S M; Devinsky, O; Grafman, J; Stein, M; Usman, M; Uhde, T W; Theodore, W H
Abstract : Clinical case reports suggest that viscosity, the behavioural tendency to talk repetitively and circumstantially about a restricted range of topics, is common in patients with temporal lobe epilepsy (TLE). Such patients are also reported to exhibit heightened levels of social cohesion, the tendency to become interpersonally "clingy". This "sticky" interpersonal style may be particularly common in TLE patients with a left sided temporal lobe seizure focus. To test this hypothesis, self-report and observer rating scales were developed to assess both viscosity and social cohesion. Subjects consisted of patients with right, left, or bilateral temporal lobe seizure foci, absence or primary generalised tonic-clonic seizures, psychiatric controls (panic disorder patients), and normal controls. Elevations on the viscosity scale were observed primarily in TLE patients with left or bilateral seizure foci. Viscosity scores also correlated with seizure duration and left handedness. No group differences were observed on the social cohesion scale. These findings are consistent with the hypothesis that viscosity results from subtle interictal language disturbances, although other pathogenetic mechanisms are discussed.